2017
DOI: 10.1038/ejcn.2017.108
|View full text |Cite
|
Sign up to set email alerts
|

The impact of multidisciplinary nutritional team involvement on nutritional care and outcomes in a medical intensive care unit

Abstract: The aim of this study was to evaluate nutritional care and outcomes in a medical intensive care unit (ICU) following multidisciplinary nutritional team (MNT) involvement. The authors retrospectively reviewed the data of all patients admitted to a medical ICU from April to October 2013 (pre-MNT period) and from April to October 2014 (post-MNT period). In total, 140 patients were included and allocated to the pre-MNT group (n=70) or the post-MNT group (n=70). The post-MNT group was more likely to use enteral nut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 8 publications
0
5
0
4
Order By: Relevance
“…Nutritional status is a principal determinant of the health trajectory and outcome following discharge from the hospital in the elderly. Clinicians need to recognize that nutritional screening is important as an integral part of clinical practice, and a standardized format is needed to identify malnutrition and ultimately its treatment [26].…”
Section: Discussionmentioning
confidence: 99%
“…Nutritional status is a principal determinant of the health trajectory and outcome following discharge from the hospital in the elderly. Clinicians need to recognize that nutritional screening is important as an integral part of clinical practice, and a standardized format is needed to identify malnutrition and ultimately its treatment [26].…”
Section: Discussionmentioning
confidence: 99%
“…For sufferers with cerebral infarction and intestinal mucosal dysfunction, dietary intake is impaired, and the effect of regular water intake is negative, requiring professionals to adapt the diet in a balanced solution [ 18 ]. Enteral nutrition support not only supports and preserves the nutrients needed by the sufferer's body and supports therapy and the impact of disease but also reduces the risk of complications and maintains the normal function of the immune system [ 19 , 20 ]. In addition, the food combination supported by enteral nutrition is rich in dietary fiber, which is easily ingested by the patients, improves the patient's diarrhea and constipation, can speed up the recovery of the disease, and ensure the patient's prognosis [ 21 ].…”
Section: Related Workmentioning
confidence: 99%
“…The presence of a NST has been shown to be effective in decreasing the infection rate, shortening the patient's ICU stay, and ensuring wound healing by providing optimal nutrition for ICU patients. 31,32 The function of the NST in addressing these undesired effects has also been shown to be a costeffective approach. 33 The daily energy and protein intake of the patients was found to be at the desired level with the intervention of the NST in the study of Jo et al 32 We found 95.5% of our patients to have sufficient calorie and daily protein intake in this study.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 The function of the NST in addressing these undesired effects has also been shown to be a costeffective approach. 33 The daily energy and protein intake of the patients was found to be at the desired level with the intervention of the NST in the study of Jo et al 32 We found 95.5% of our patients to have sufficient calorie and daily protein intake in this study. We believe the reason was the evaluation of the nutritional state of the patients twice a day by the NST, similar to that reported in the literature.…”
Section: Discussionmentioning
confidence: 99%